Proposed Business Strategy: Capturing Opportunities In Epoxy Business On Indonesia (A Case Study of PT.Sumber Mukti Jaya Makmur (The Indonesian Journal of Business Administration, 2021)
PT. Sumber Mukti Jaya Makmur is a construction company that has long been engaged in painting buildings, machinery and pipes, established since 1991 in the Purwakarta area. Over time the demand for painting increased not only on ordinary painting but more specifically on floor coatings or commonly called epoxy flooring. On this occasion the authors conducted a survey and literacy study on the epoxy flooring industry and the demand for epoxy flooring which continues to increase every year and the availability of local professional contractors in the Purwakarta area. The purpose of this research is to know the business conditions of epoxy both internally and externally, as well as capture business opportunities in the epoxy industry and determine the appropriate and ideal business strategy for Sumber Mukti. The method used in explaining external conditions is Industrial Organizational Model (I/O), determination of attractive industry based on Industry Analysis, internal condition analysis through resources, capabilities and core competencies and then summarized in SWOT analysis. The results showed that the epoxy business is less attractive, so as a company that is just entering the industry must find market gaps by segmenting and differentiating the business model as a proposed strategy in order to meet the need and wants of Sumber Mukti customers.Keywords : Epoxy business opportunities, Industrial Organizational Model, Industry Analysis, Attractiveness Industry, SWOT Analysis